COVID-19 and populism a critical discourse analysis of populist discourses in Rodrigo Duterte's speeches from March to August 2020 of the COVID-19 pandemic - Bola, Rio Angela M.; Ramboa, Jasmine Sabrina J.
Recent years have shown a rise in populism, a political logic that works by constructing divisions between “the people” and perceived enemies such as elites, critics, or outsiders. While populism can be employed in many issues, it has been especially prevalent in health crises like the COVID-19 pandemic, where uncertainty and urgency create fertile ground for populist rhetoric to flourish (Lasco & Curato, 2019). This study aimed to explain how former President Rodrigo Duterte employed populist communication in his national addresses during the early months of the pandemic. Through Fairclough’s (1995) Critical Discourse Analysis (CDA) framework and De Vreese et al.’s (2018) Populist Communication Theory, this study analyzed a total of 18 speeches from March to August 2020 to reveal how Duterte discursively constructed political actors and legitimized his power in the context of a public health emergency. Guided by literature on populist ideology and style, this study found that Duterte reinforced populist communication in his speeches through his constructions of good citizens against unhelpful elites and reckless ‘others’ while also positioning himself as the protector of the people. This study provides insights into how leaders utilize populist discourses to shape public perception and justify exceptional measures during a health crisis.